INVESTIGATING IN DIFFICULTIES EN- COUNTER STUDENTS OF IRAQI SEC- ONDARY SCHOOL WHEN USING PRO- NOUNS IN ENGLISH LANGUAGE - SALEH, AHMED MUAFAQ AHMED MUAFAQ (International Journal of Psychosocial Rehabilitation, 2020)
— Language is the main tool of communication between the people over the world. So, teaching and learning a language is essential thing for everyone to be able to communicate and understand what others say and want.in English language. There are four skills we need to master them; listening, speaking, reading, writing. A pronoun is considered part of these skills to be learned. Pronouns are used instead of people or things. Pronouns can be divided into many types such as subject pronouns, object pronouns, possessive pronoun and possessive adjective. The current study aims to investigate the difficulties students encounter in Iraqi secondary schools when using pronouns in English language in 2018-2019.the sample of this study was 35 that have chosen from Al-Yamen secondary school for boys from the population of 4th class that were 65. This study used the descriptive-analytical method to analze the data which has gathered through a test applied on students. The findings show that students still have problems and difficulties in distinguishing between the types of pronouns: subject pronouns, object pro- nouns, possessive pronouns and possessive adjectives and of how choose the correct and appropriate pronoun. As a result of this study, students are still having some difficulties of 4th class in Al-Yamen secondary school in using pronouns.so, there are some suggestions have been included in this study to help the teacher in decreasing those difficulties.